Ruthenium-iridium composite electrode prepared by electrochemical codeposition method as well as preparation method and application of ruthenium-iridium composite electrode

The electrochemical co-deposition method is used to grow TiO2 nanotubes on the titanium substrate and deposit ruthenium and iridium in it to form a nanocrystal structure, which solves the problem of easy peeling and high cost of ruthenium iridium titanium electrodes in traditional coating processes, and realizes the High catalytic activity and long life ruthenium iridium composite electrode.

CN119287445APending Publication Date: 2025-01-10ZHEJIANG UNIV OF TECH

Patent Information

Application Number
CN202411429524.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The ruthenium iridium titanium electrode prepared by the traditional coating process is prone to coating peeling, passivation and dissolution after long-term use, resulting in attenuation of the electrode catalytic activity, and the production cost is high, the process is complex, which affects the electrode life.

Method used

The ruthenium iridium composite electrode was prepared by electrochemical co-deposition method. By growing TiO2 nanotubes in situ on a titanium substrate as an intermediate layer, adding trace amounts of antimony ions and sodium nitrate, it promotes the deposition of ruthenium and iridium in the nanoTiO2 tubes to form a nanocrystalline structure. And it is fully oxidized during heat treatment to form a ruthenium iridium oxide with chlorine-activating activity.

Benefits of technology

The process flow is simplified, the utilization rate of precious metal raw materials is improved, the catalytic activity and stability of the electrode is enhanced, the service life of the electrode is extended, the chlorine analysis current is high, and the strengthening life is more than 580 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287445A_ABST
    Figure CN119287445A_ABST
Patent Text Reader

Abstract

The invention discloses a ruthenium-iridium composite electrode prepared by an electrochemical codeposition method and a preparation method and application thereof, and the preparation method of the ruthenium-iridium composite electrode comprises the following steps: 1) taking a titanium sheet as an anode, taking a platinum electrode or graphite as a cathode, and placing the anode and the cathode in an aqueous solution containing F <-> for anodic oxidation; (2) putting the sample subjected to anodic oxidation into a tube furnace, and carrying out heat treatment in argon or nitrogen to obtain an anatase type TiO2 nanotube; 3) taking the TiO2 nanotube as a cathode, and controlling a certain current in an aqueous solution containing Ru salt, Ir salt, NaNO3 and a small amount of SbCl3 for co-deposition to obtain Ru and Ir nanocrystals; and 4) fully oxidizing the sample deposited with the Ru and Ir nanocrystals at a certain temperature to obtain the ruthenium-iridium composite metal oxide electrode. The method is short in technological process and high in precious metal raw material utilization rate, and the prepared ruthenium-iridium composite metal oxide electrode has the advantages of being high in chlorine evolution electrocatalytic activity and long in service life. As an electrode material, the material has important application prospects and is suitable for the fields of chlor-alkali industry, water treatment, metallurgy and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanocomposite materials, and in particular to a ruthenium-iridium composite electrode prepared by an electrochemical co-deposition method, a preparation method and an application thereof. Background Art

[0002] Titanium-based metal oxide is a kind of insoluble anode material developed in the 1960s. It has good corrosion resistance and electrochemical properties, and the finished product has high stability. Therefore, it is widely used in metallurgy, chemical industry, environmental protection and various corrosive environments. Titanium-based composite metal electrodes are mainly used in the chlor-alkali industry. The ruthenium-iridium-titanium electrode prepared by coating ruthenium-iridium metal oxide on titanium-based metal is a composite metal electrode. Among them, the ruthenium-iridium composite metal coating is a multi-element coating, and its main purpose is to reduce the chlorine evolution potential, thereby increasing the electrode life.

[0003] Ruthenium-iridium-titanium electrodes prepared by traditional coating processes will fail due to coating peeling, passivation, and corrosion after long-term use. The reasons for the failure can be attributed to: (1) Insufficient bonding between the active coating and the substrate, causing the coating to peel off. (2) There are often large cracks on the surface of the coated electrode. During use, the electrolyte will penetrate into the substrate through the cracks, causing the substrate to passivate and the electrode catalytic activity to decay.

[0004] In the disclosed patent (A ruthenium-tantalum chlorine evolution electrode and its preparation method and testing method (ZL201910679669.0), an improved coating process is adopted, and titanium dioxide nanotubes are used as the intermediate layer, which can avoid the cracks caused by the heat shrinkage effect of the traditional coating process and improve the service life of the chlorine evolution electrode. However, due to the long coating process and large raw material loss, the production cost of precious metal electrodes is high.

[0005] Therefore, how to improve the manufacturing process, reduce the manufacturing cost, and extend the service life of the electrode in the manufacturing process of ruthenium-iridium-titanium electrodes has always been a difficult problem that has troubled many researchers. Summary of the invention

[0006] In view of the above technical problems existing in the existing ruthenium-iridium-titanium electrode, the purpose of the present invention is to provide a ruthenium-iridium composite electrode prepared by an electrochemical co-deposition method and its preparation method and application. The electrodeposition process of ruthenium-iridium nanocrystals adopted by the present invention has the characteristics of short process flow and high raw material utilization rate. Trace antimony ions and sodium nitrate are introduced to promote the nucleation of electrocrystallization and refine the grains, which is beneficial to the deposition of ruthenium and iridium in the nano-TiO2 tube. At the same time, the ruthenium-iridium with nanocrystalline structure can be fully oxidized in the further heat treatment process to generate ruthenium-iridium oxide with chlorine evolution activity, thereby improving the catalytic performance of the electrode.

[0007] The technical solution adopted by the present invention is as follows:

[0008] A method for preparing a ruthenium-iridium composite electrode by electrochemical co-deposition, the method comprising the following steps:

[0009] 1) Pre-treating the titanium sheet, i.e. grinding and chemical polishing, using the treated titanium sheet as an anode and the graphite sheet as a cathode, applying power in an electrochemical device for anodization, and washing and drying after anodization;

[0010] 2) The anodized titanium sheet in step 1) is placed in a tubular furnace for heat treatment, slowly heating from room temperature to 400-500°C at a heating rate of 5-10°C / min, then kept warm for 2-3 hours, and cooled to room temperature with the furnace to obtain TiO2 nanotubes grown on the surface of the titanium sheet, which are denoted as TiO2NTs.

[0011] 3) using the TiO2NTs obtained in step 2) as a cathode and another conductive material as an anode, using (NH4)2SO4 solution as an electrolyte, performing reduction doping by electrolysis reaction, and then electrochemically co-depositing the cathode and anode in a deposition solution containing Ru salt, Ir salt, grain refiner and a small amount of nucleation promoter;

[0012] 4) The cathode electrode sheet obtained after the co-deposition in step 3) is placed in a muffle furnace for calcination and full oxidation treatment, and finally cooled in the furnace to obtain a ruthenium-iridium composite metal oxide electrode.

[0013] Preferably, the titanium sheet used in step 1) has a titanium content of more than 99.5 wt %, and is polished in stages using 400 mesh, 600 mesh, 800 mesh, 1000 mesh, 1200 mesh, 1500 mesh and 2000 mesh sandpaper until there are no coarse scratches on its surface.

[0014] Preferably, the chemical polishing of the titanium sheet in step 1) is to place the polished titanium sheet in an aqueous solution containing 70-80 g / LCrO3 and 1-5 wt% HF for reaction for 10-20 min at a reaction temperature of 45±55°C until the surface is bright.

[0015] Preferably, in the electrochemical device described in step 1), the electrolyte is an aqueous solution containing 1-5wt% HF, the pretreated titanium sheet is used as the anode, the graphite electrode or the platinum electrode is used as the cathode, the anodic oxidation voltage is 20-30V, the time is 20-30min, and the temperature is 20-30°C.

[0016] Preferably, the TiO2NTs described in step 3) are reduction-doped in a certain concentration of (NH4)2SO4 solution, wherein the concentration of the (NH4)2SO4 solution is 0.8 to 1.2 mol / L, the reduction-doping potential is -1.3 to -1.6 V, and the reduction-doping time is 10 to 60 s, preferably 25 to 40 s.

[0017] Preferably, in step 3), Ru salt and Ir salt are used as main salts in the deposition solution, wherein the Ru salt is one or more of ruthenium trichloride, ruthenium nitrate and ruthenium acetate, preferably ruthenium trichloride; and the Ir salt is one or more of iridium trichloride, chloroiridic acid and ammonium iridate, preferably iridium trichloride.

[0018] Preferably, the total concentration of Ru salt and Ir salt in the deposition solution in step 3) is (1-5)×10 -3 mol / L, preferably (2 to 5)×10 -3 mol / L, the molar ratio of Ru salt to Ir salt is 1-2.5:1.

[0019] Furthermore, a grain refiner is added to the main salt solution. The grain refiner is one or more of sodium nitrate, titanium boron refiner, and aluminum titanium boron block, preferably sodium nitrate, and the concentration thereof is 10 to 50 g / L, preferably 20 to 40 g / L.

[0020] Furthermore, a nucleation promoter is added to the main salt solution. The nucleation promoter is antimony trichloride, and its concentration is 0.5 to 3×10 -4 mol / L, preferably 1 to 2×10 -4 mol / L.

[0021] Preferably, the process conditions described in step 3) refer to deposition time, deposition temperature, and current density. The constant current density of electrochemical co-deposition is 0.5-5 mA / cm 2 , preferably 1 to 3 mA / cm 2 ; The deposition temperature is 10-30°C, preferably 25±1°C; the deposition time is 1-10h, preferably 5-7h.

[0022] Preferably, in step 4), the calcination temperature is 400-550° C., preferably 500±10° C.; the holding time at the calcination temperature is 1-5 h, preferably 2-3 h.

[0023] The present invention also provides an application of a ruthenium-iridium composite electrode prepared by an electrochemical co-deposition method as an anode in an electrocatalytic chlorine evolution reaction. The application method is: in a 0.5-1.5 mol / L NaCl (pH adjusted to 1-3) electrolyte, the ruthenium-iridium composite electrode is used as an anode and a titanium sheet is used as a cathode. The current density of the electrolysis process is 0.5-1 mA / cm 2 The electrolyte temperature is 40±1℃, and the electrolysis time when the voltage of the electrolytic cell increases by 5V under constant current electrolysis conditions is taken as the enhanced life of the electrode.

[0024] The above scheme of the present invention has the following beneficial effects:

[0025] 1. The present invention uses TiO2 nanotubes grown in situ on a titanium substrate as an intermediate layer, and loads Ru and Ir in the pores of the intermediate layer by electrochemical co-deposition. The process route is short, the utilization rate of precious metal raw materials is high, and the prepared composite electrode has good catalytic activity and stability.

[0026] 2. In order to promote the deposition of Ru and Ir particles in TiO2 nanotubes, the present invention adds a grain refiner and a nucleation promoter to the electrolyte, so that the Ru and Ir nanocrystals generated by electroreduction are uniformly loaded in the TiO2 nanotubes, forming an organic bond and enhancing the bonding force.

[0027] 3. The Ru and Ir particles deposited by the electrochemical method in the present invention are single precious metals (without electrocatalytic chlorine evolution activity) and are not easily oxidized to generate catalytically active components RuO2 and IrO2 ( Figure 2 As shown). Ru and Ir nanocrystals generated by optimizing the electrodeposition process can be fully oxidized at a lower temperature ( Figure 1 As shown), the collapse of TiO2 nanotubes caused by oxidation at high temperature is avoided.

[0028] 4. The ruthenium-iridium composite electrode prepared on TiO2 nanotubes by electrochemical co-deposition in the present invention has excellent electrocatalytic performance, high chlorine evolution current, and enhanced life of more than 580 hours.

[0029] Compared with the patent CN201910679669.0 previously applied for by the applicant, the present invention fills ruthenium and iridium in nanotubular titanium dioxide by a one-step electrodeposition method, which simplifies the steps and reduces the waste of raw materials, thus achieving further progress. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is the XRD pattern of the ruthenium-iridium composite electrode prepared in the fourth step of Example 1 of the present invention;

[0031] Figure 2 The XRD pattern of the ruthenium-iridium composite electrode prepared in the fourth step of comparative example 1 of the present invention;

[0032] Figure 3 CV curve comparison diagram of the ruthenium-iridium composite electrode prepared by electrochemical co-deposition method in Example 1 of the present invention and Comparative Example 1;

[0033] Figure 4 This is a comparison chart of the enhanced life of the ruthenium-iridium composite electrode prepared by the electrochemical co-deposition method in Example 1 of the present invention and the commercial ruthenium-iridium electrode. DETAILED DESCRIPTION

[0034] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0035] Embodiment 1:

[0036] (1) A titanium sheet with a thickness of 1 mm and a purity of ≥99.5% was used as a substrate (the length of the titanium sheet substrate was 2 cm and the width was 1.5 cm, the same below). The surface was pretreated by grinding with sandpaper of 400 mesh, 600 mesh, 800 mesh, 1000 mesh, 1200 mesh, 1500 mesh and 2000 mesh in a step-by-step manner, and then placed in an aqueous solution containing 75 g / L CrO3 and 4 wt% HF for chemical polishing at a reaction temperature of 50°C for a reaction time of 15 min until the surface was bright, thereby obtaining a pretreated titanium sheet.

[0037] The pretreated titanium sheet was used as the anode and the graphite sheet as the cathode (the length of the graphite cathode was 10 cm and the width was 3 cm, the same below). Power was applied to the electrochemical device for anodic oxidation. The electrolyte for anodic oxidation was an aqueous solution containing 1 wt% HF. The constant voltage was 25 V, the time was 20 min, and the temperature was 25°C. The samples after anodic oxidation were ultrasonically cleaned and dried.

[0038] (2) placing the titanium sheet anodized in step (1) in a tube furnace and heating it to 450° C., controlling the heating rate to be 5° C. / min, then keeping it at 450° C. for 2 h, and then slowly cooling it to room temperature, thereby obtaining TiO2 nanotubes on the surface of the titanium sheet, which are referred to as TiO2NTs;

[0039] (3) Using the TiO2NTs obtained in step 2) as the cathode and the platinum electrode as the anode, reduction doping was performed by electrolysis in a 1 mol / L (NH4)2SO4 solution, the reduction doping potential was -1.5 V, the reduction doping time was 30 s, and then the cathode and the anode were placed in a 2×10 -3 mol / LRuCl3、2×10 -3 mol / LIrCl3, 40g / L sodium nitrate and 1×10 -4 mol / LSbCl3 electrolyte (the solvent of the electrolyte is water, the same below) with a constant current (2mA / cm 2 ) sedimentation for 6 h;

[0040] (4) placing the cathode electrode sheet obtained in step (3) in a muffle furnace and heating it to 500° C., controlling the heating rate to 10° C. / min, then keeping it at 500° C. for 3 h, and finally cooling it in the furnace and taking it out to obtain a ruthenium-iridium composite metal oxide electrode.

[0041] Experiment of electrocatalytic chlorine evolution reaction: The test was conducted on an electrochemical workstation, with the ruthenium-iridium composite electrode prepared in Example 1 as the anode, the polished titanium sheet as the cathode, and the saturated calomel electrode as the reference electrode. The electrolysis process was carried out in an electrolytic cell, the electrolyte was a 1 mol / L NaCl solution, the solution pH was adjusted to 2, and the electrolyte temperature was maintained at 40±1°C.

[0042] According to the above electrocatalytic chlorine evolution conditions, the chlorine evolution performance was studied by observing the chlorine evolution current at a potential of 0-1.2V. The CV curve test results were obtained. Figure 3 The experimental results show that the electrode has good electrocatalytic chlorine evolution activity, and the chlorine evolution current is 172mA / cm at a potential of 1.2V. 2 Comparing the chlorine evolution current at a potential of 1.2 V, the higher the current, the greater the activity.

[0043] According to the above electrocatalytic chlorine evolution conditions, the constant current was 600 mA / cm 2 When the electrolysis reaction is carried out under the conditions of Figure 4 , with a constant current of 600mA / cm 2 The electrolysis time when the voltage of the electrolytic cell increases by 5V under electrolysis conditions is taken as the enhanced life of the electrode. Figure 4 It can be seen that when the ruthenium-iridium composite electrode prepared in Example 1 is used as the anode, the enhanced life span exceeds 580 hours (that is, the electrode has not failed at 580 hours and the electrode is very stable).

[0044] In addition, a commercial ruthenium-iridium electrode (the electrode is composed of ruthenium-iridium-titanium, purchased from Shaanxi Maizeheng Metal Co., Ltd.) was used as a control, replacing the "ruthenium-iridium composite electrode prepared in Example 1" as the anode, and the chlorine was electrocatalyzed under the above conditions at a constant current of 600 mA / cm 2 When the electrolysis reaction is carried out under the conditions of Figure 4 .

[0045] Figure 4 The enhanced life of the ruthenium-iridium composite electrode prepared by the electrochemical co-deposition method in Example 1 of the present invention and the commercial ruthenium-iridium electrode were compared. Figure 4 Test electrode life, high current (600mA / cm 2 ) is tested. As the test time increases, it can be seen that the electrode performance of the commercial ruthenium-iridium electrode gradually deteriorates, and the voltage rises sharply when it finally fails. In the present invention, a voltage rise of more than 5V is considered to be an electrode failure (such as Figure 4 The middle red line, after more than 200 hours, the voltage rises sharply and finally fails).

[0046] Commercial ruthenium-iridium electrodes are usually prepared by coating a mixed coating of ruthenium oxide, iridium oxide and titanium dioxide. In contrast, the present invention first prepares nano-tubular titanium dioxide, then deposits metallic ruthenium and iridium in the nano-titanium dioxide, and finally calcines at high temperature to obtain an active layer containing ruthenium, iridium and titanium oxides, which has better electrode performance.

[0047] Comparative Example 1:

[0048] (1) A titanium sheet with a thickness of 1 mm and a purity of ≥99.5% is used as a substrate for surface pretreatment. The surface pretreatment is performed by grinding with sandpaper of 400 mesh, 600 mesh, 800 mesh, 1000 mesh, 1200 mesh, 1500 mesh and 2000 mesh in a step-by-step manner, and then chemically polished in an aqueous solution of 75 g / LCrO3 and 4 wt% HF. The reaction temperature is 50°C and the reaction time is 15 min until the surface is bright, thereby obtaining a pretreated titanium sheet. The pretreated titanium sheet is used as an anode and graphite is used as a cathode. Electricity is applied to an electrochemical device for anodization. The electrolyte for anodization is an aqueous solution containing 1 wt% HF. The constant voltage is 25 V, the reaction time is 20 min, and the temperature is 25°C. The sample after anodization is ultrasonically cleaned and dried.

[0049] (2) placing the titanium sheet anodized in step (1) in a tube furnace and heating it to 450° C., controlling the heating rate to be 5° C. / min, then keeping it at 450° C. for 2 h and slowly cooling it to room temperature, thereby obtaining a titanium dioxide nanotube (TiO2) array structure on the surface of the titanium sheet, which is referred to as TiO2-NTs;

[0050] (3) Using the TiO2NTs obtained in step 2) as the cathode and the platinum electrode as the anode, reduction doping was performed by electrolysis in a 1 mol / L (NH4)2SO4 solution. The reduction doping potential was -1.5 V and the reduction doping time was 30 s. Then, RuCl3 (2×10 -3 mol / L)、IrCl3(2×10 -3 mol / L) in a constant current (2 mA / cm 2 ) was deposited for 6 h; the difference from Example 1 is that no grain refiner and nucleation promoter were added to the deposition liquid.

[0051] (4) placing the cathode electrode sheet obtained in step (3) in a muffle furnace and heating it to 500° C., controlling the heating rate to 10° C. / min, then keeping it at 500° C. for 3 h, and finally cooling it in the furnace and taking it out to obtain a ruthenium-iridium composite metal oxide electrode.

[0052] The experiment of electrocatalytic chlorine evolution reaction in Control Example 1 is the same as that in Example 1, except that the anode is replaced by the ruthenium-iridium composite electrode in Control Example 1, and the other conditions remain unchanged. The chlorine evolution performance is studied by observing the chlorine evolution current at a potential of 0-1.2V, and the CV curve test results are shown in Table 1. Figure 3 The chlorine evolution current at a potential of 1.2 V is 83 mA / cm 2 , constant current 600mA / cm 2 The enhanced life measured under electrolytic conditions is 335h.

[0053] Comparison of the experimental results of Example 1 of the present invention with those of Control Example 1 shows that the ruthenium-iridium composite electrode prepared by the present invention significantly improves the catalytic performance and service life.

[0054] The XRD pattern of the product prepared in the fourth step of Example 1 is shown in Figure 1 The XRD pattern of the product prepared in the fourth step of comparative example 1 is shown in Figure 2 , Figure 1 It can be seen that the main peaks are all oxides of ruthenium and iridium metals. Figure 2 It can be seen that the main peak contains both ruthenium iridium metal oxides and ruthenium iridium metal elements. Ruthenium iridium metal oxides are the main catalysts for chlorine evolution electrodes, and the presence of elemental forms will reduce the chlorine evolution performance of the electrode. Therefore, the addition of nucleation promoters and grain refiners can effectively prepare electrodes with better chlorine evolution performance (ruthenium iridium metal oxides).

[0055] Embodiment 2:

[0056] (1) Repeat step (1) in Example 1;

[0057] (2) Repeat step (2) in Example 1;

[0058] (3) The TiO2NTs obtained in step (2) were placed in a -3 mol / LRuCl3、2×10 -3 mol / LIrCl3, 40g / L sodium nitrate and 1×10 -4 mol / L SbCl3 electrolyte (the solvent of the electrolyte is water, the same below) with a constant current (2mA / cm 2 ) was deposited for 6 hours; the difference from Example 1 is that no reduction doping operation in (NH4)2SO4 solution was performed before constant current electrodeposition.

[0059] (4) Repeat step (4) in Example 1.

[0060] The experiment of electrocatalytic chlorine evolution reaction in Example 2 is the same as that in Example 1, except that the anode is replaced by the ruthenium-iridium composite electrode in Example 2, and the other conditions remain unchanged. The experimental results show that the chlorine evolution current is 110 mA / cm at a potential of 1.2 V. 2 , constant current 600mA / cm 2 The enhanced life measured under electrolytic conditions is 330h.

[0061] By comparing the experimental results of Example 1 and Example 2 of the present invention, it can be seen that if the step of performing reduction doping in the (NH4)2SO4 solution is omitted, the catalytic performance of the prepared electrode is poor. This is because after the reduction doping, the impedance of the electrode sheet will be reduced, making it easier to deposit ruthenium and iridium metal ions on the electrode sheet during electrochemical co-deposition.

[0062] Embodiment 3:

[0063] (1) Repeat step (1) in Example 1;

[0064] (2) Repeat step (2) in Example 1;

[0065] (3) The TiO2NTs obtained in step (2) were reduction-doped in a 1 mol / L (NH4)2SO4 solution at a reduction-doping potential of -1.5 V for 30 s, and then in a solution containing 2×10 -3 mol / LRuCl3、2×10 -3 mol / LIrCl3, 40g / L sodium nitrate and 1×10 -4 mol / L SbCl3 electrolyte with constant current (2mA / cm 2 ) was deposited for 5 h; the difference from Example 1 is that the deposition time was changed to 5 h.

[0066] (4) Repeat step (4) in Example 1.

[0067] The experiment of electrocatalytic chlorine evolution reaction in Example 3 is the same as that in Example 1, except that the anode is replaced by the ruthenium-iridium composite electrode in Example 3, and the other conditions remain unchanged. The chlorine evolution current at a potential of 1.2 V is 150 mA / cm 2 , constant current 600mA / cm 2 The enhanced life measured under electrolytic conditions is 510h.

[0068] Embodiment 4:

[0069] (1) Repeat step (1) in Example 1;

[0070] (2) Repeat step (2) in Example 1;

[0071] (3) The TiO2NTs obtained in step (2) were reduction-doped in a 1 mol / L (NH4)2SO4 solution at a reduction-doping potential of -1.5 V for 30 s, and then in a solution containing 2×10 -3 mol / LRuCl3、2×10 -3 mol / LIrCl3, 40g / L sodium nitrate and 1×10 -4 mol / L SbCl3 electrolyte with constant current (2mA / cm 2 ) was deposited for 4 hours; the difference from Example 1 is that the deposition time was changed to 4 hours.

[0072] (4) Repeat step (4) in Example 1.

[0073] The experiment of electrocatalytic chlorine evolution reaction in Example 4 is the same as that in Example 1, except that the anode is replaced by the ruthenium-iridium composite electrode in Example 4, and the other conditions remain unchanged. The chlorine evolution current at a potential of 1.2 V is 132 mA / cm 2 , constant current 600mA / cm 2 The strengthening life measured under electrolytic conditions is 480h.

[0074] Embodiment 5:

[0075] (1) Repeat step (1) in Example 1;

[0076] (2) Repeat step (2) in Example 1;

[0077] (3) The TiO2NTs obtained in step (2) were reduction-doped in a 1 mol / L (NH4)2SO4 solution at a reduction-doping potential of -1.5 V for 30 s, and then in a solution containing 2×10 -3 mol / LRuCl3、2×10 -3 mol / LIrCl3, 30g / L sodium nitrate and 1×10 -4 mol / L SbCl3 electrolyte with constant current (2mA / cm 2 ) was deposited for 6 hours; the difference from Example 1 is that the solution concentration of the grain refiner was changed to 30 g / L.

[0078] (4) Repeat step (4) in Example 1.

[0079] The experiment of electrocatalytic chlorine evolution reaction in Example 5 is the same as that in Example 1, except that the anode is replaced by the ruthenium-iridium composite electrode in Example 5, and the other conditions remain unchanged. The chlorine evolution current at a potential of 1.2 V is 142 mA / cm 2 , constant current 600mA / cm 2 The enhanced life measured under electrolytic conditions is 495h.

[0080] Embodiment 6:

[0081] (1) Repeat step (1) in Example 1;

[0082] (2) Repeat step (2) in Example 1;

[0083] (3) The TiO2NTs obtained in step (2) were reduction-doped in a 1 mol / L (NH4)2SO4 solution at a reduction-doping potential of -1.5 V for 30 s, and then in a solution containing 2×10 -3 mol / LRuCl3、2×10 -3mol / LIrCl3, 40g / L sodium nitrate and 1.5×10 -4 mol / L SbCl3 electrolyte with constant current (2mA / cm 2 ) was deposited for 6 h; the difference from Example 1 was that the solution concentration of the nucleation promoter was changed to 1.5×10 -4 mol / L.

[0084] (4) Repeat step (4) in Example 1.

[0085] The experiment of electrocatalytic chlorine evolution reaction in Example 6 is the same as that in Example 1, except that the anode is replaced by the ruthenium-iridium composite electrode in Example 6, and the other conditions remain unchanged. The chlorine evolution current at a potential of 1.2 V is 135 mA / cm 2 , constant current 600mA / cm 2 The enhanced life measured under electrolytic conditions is 450h.

[0086] Embodiment 7:

[0087] (1) Repeat step (1) in Example 1;

[0088] (2) Repeat step (2) in Example 1;

[0089] (3) The TiO2NTs obtained in step (2) were reduction-doped in a 1 mol / L (NH4)2SO4 solution at a reduction-doping potential of -1.5 V for 30 s, and then in a solution containing 2×10 -3 mol / LRuCl3、8.6×10 -4 mol / LIrCl3, 40g / L sodium nitrate and 1×10 -4 mol / L SbCl3 electrolyte with constant current (2mA / cm 2 ) was deposited for 6 hours; the difference from Example 1 is that the ratio of ruthenium to iridium solution was changed to Ru:Ir=7:3.

[0090] (4) Repeat step (4) in Example 1.

[0091] The experiment of electrocatalytic chlorine evolution reaction in Example 7 is the same as that in Example 1, except that the anode is replaced by the ruthenium-iridium composite electrode in Example 7, and the other conditions remain unchanged. The electrocatalytic chlorine evolution current at a potential of 1.2 V is 142 mA / cm 2 , constant current 600mA / cm 2 The strengthening life measured under electrolytic conditions is 520h.

[0092] Through 7 examples and 1 control experiment, it can be clearly seen that by combining a specific ruthenium-iridium solution concentration ratio with a grain refiner and a nucleation promoter, the ruthenium-iridium composite electrode prepared by the electrochemical co-deposition method can play a significant role in the electrocatalytic chlorine evolution activity and life.

Claims

1. A method for preparing a ruthenium-iridium composite electrode by electrochemical co-deposition, characterized in that The following steps are involved: 1) The titanium sheet is used as the anode after surface pretreatment, and another conductive material is used as the cathode. The electrochemical device is powered for anodic oxidation. The electrolyte in the electrochemical device is F-containing - The anodized sample was ultrasonically cleaned and dried. 2) placing the titanium sheet anodized in step 1) in a tube furnace for heat treatment to obtain anatase TiO2 nanotubes on the surface of the titanium sheet, which are referred to as TiO2NTs; 3) Using the TiO2NTs obtained in step 2) as a cathode and another conductive material as an anode, using (NH4)2SO4 solution as an electrolyte, performing reduction doping by electrolysis reaction, and then electrochemically co-depositing the cathode and the anode in a deposition solution containing Ru salt, Ir salt, a grain refiner and a small amount of nucleation promoter; 4) The cathode electrode sheet obtained in step 3) is placed in a muffle furnace for calcination and full oxidation treatment to obtain a ruthenium-iridium composite metal oxide electrode.

2. The method for preparing a ruthenium-iridium composite electrode by electrochemical co-deposition as claimed in claim 1, characterized in that Step 1) The step of pre-treating the surface of the titanium sheet includes: firstly grinding the surface of the titanium sheet with sandpaper, and then chemically polishing the surface in an aqueous solution containing 70-80 g / L CrO3 and 1-5 wt% HF, the reaction temperature is 45±55°C, the reaction time is 10-20 min, until the surface is bright; Step 1) The process conditions of anodization are that the electrolyte is an aqueous solution containing 1-5 wt% HF, the pretreated titanium sheet is used as the anode, the graphite electrode or the platinum electrode is used as the cathode, the anodization voltage is 20-30 V, the time is 20-30 min, and the temperature is 20-30° C.

3. The method for preparing a ruthenium-iridium composite electrode by electrochemical co-deposition as claimed in claim 1, characterized in that In step 2), the heat treatment process is to control the heating rate to 5-10°C / min, from room temperature to a constant temperature heat treatment temperature of 400-500°C, and the holding time is 2-3h, after which the sample is cooled to room temperature with the furnace.

4. The method for preparing a ruthenium-iridium composite electrode by electrochemical co-deposition as claimed in claim 1, characterized in that In step 3), TiO2NTs are reduction-doped in a certain concentration of (NH4)2SO4 solution, wherein the concentration of the (NH4)2SO4 solution is 0.8~1.2 mol / L, the reduction-doping potential is -1.3~-1.6 V, and the reduction-doping time is 10~60 s, preferably 25~40 s.

5. The method for preparing a ruthenium-iridium composite electrode by electrochemical co-deposition as claimed in claim 1, characterized in that Step 3) Ru salt and Ir salt are used as main salts in the deposition solution, the Ru salt is one or more of ruthenium trichloride, ruthenium nitrate and ruthenium acetate, preferably ruthenium trichloride; the Ir salt is one or more of iridium trichloride, chloroiridic acid and ammonium iridate, preferably iridium trichloride; The total concentration of Ru salt and Ir salt in the deposition solution is (1~5)×10 -3 mol / L, preferably (2~5)×10 -3 mol / L, the molar ratio of Ru salt to Ir salt is 1-2.5:1; The grain refiner in the deposition liquid is one or more of sodium nitrate, titanium boron refiner, and aluminum titanium boron block, preferably sodium nitrate, and its concentration in the deposition liquid is 10-50 g / L, preferably 20-40 g / L; The nucleation promoter in the deposition solution is antimony trichloride, and its concentration is 0.5~3×10 -4 mol / L, preferably 1~2×10 -4 mol / L.

6. The method for preparing a ruthenium-iridium composite electrode by electrochemical co-deposition as claimed in claim 1, characterized in that The process conditions of electrochemical co-deposition in step 3) are: the constant current density of electrochemical co-deposition is 0.5~5mA / cm 2 , preferably 1~3mA / cm 2 ; The deposition temperature is 10~30℃, preferably 25±1℃; the deposition time is 1~10h, preferably 5~7h.

7. The method for preparing a ruthenium-iridium composite electrode by electrochemical co-deposition as claimed in claim 1, characterized in that In step 4), the calcination temperature is 400-550° C., preferably 500±10° C.; the holding time at the calcination temperature is 1-5 h, preferably 2-3 h.

8. A ruthenium-iridium composite electrode prepared by an electrochemical co-deposition method according to any one of claims 1 to 7.

9. Use of a ruthenium-iridium composite electrode prepared by an electrochemical co-deposition method as claimed in claim 8 as an anode in an electrocatalytic chlorine evolution reaction.

10. The use according to claim 9, characterized in that The ruthenium-iridium composite electrode is used as the anode and the titanium sheet is used as the cathode. The electrolysis process is carried out in an electrolytic cell. The electrolyte is a 0.5-1.5 mol / L NaCl solution. The solution pH is adjusted to 1-3. The electrolyte temperature is 30-50°C. The current density of the electrolysis process is 0.5-1 mA / cm 2 .

Citation Information

Patent Citations

  • Ruthenium-tantalum chlorine-evolution electrode and preparation method and testing method thereof

    CN110387558A

Cited By

  • Chlorine evolution electrode and preparation method and application thereof

    CN121317967A